2018
DOI: 10.2138/am-2018-6415
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline apatites: The fundamental role of water

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 79 publications
(108 reference statements)
2
53
0
1
Order By: Relevance
“…3) the proportion of surface layer appears more important in BNA than in CDHA. This result also agrees with the synthesis conditions (maturation at 37°C during 30 min for CDHA and only 22°C for 5 min for BNA), the higher the maturation time and temperature are, the thinner is the non apatitic hydrated surface layer [7]. The crystalline core is a calcium (and hy droxide) deficient apatite which contains apatitic hydrogenphosphate ions (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…3) the proportion of surface layer appears more important in BNA than in CDHA. This result also agrees with the synthesis conditions (maturation at 37°C during 30 min for CDHA and only 22°C for 5 min for BNA), the higher the maturation time and temperature are, the thinner is the non apatitic hydrated surface layer [7]. The crystalline core is a calcium (and hy droxide) deficient apatite which contains apatitic hydrogenphosphate ions (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…environments and the nanosized dimensions of the crystals [21]. In the consolidation process of ceramics at such low temperature, the role of the hydrated layer is thought to be primordial: the ions contained in the hydrated layer being indeed highly labile, ion diffusion through hy drated layers of adjacent nanocrystals can occur even without strong thermal activation [7]. Recently, we investigated consolidation of bone like carbonated calcium phosphates by SPS at low temperature and showed that the sinterability was greatly enhanced when amorphous carbonated calcium phosphate (ACPs) powders were used in compar ison with nanocrystalline ones [23].…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongly bound water molecules are very likely to form a rigid hydration shell around the bone mineral platelets such that their largest side faces are not in direct contact with each other. As for trapped water molecules, they presumably form hydration spheres around the surface ions in a configuration that is reminiscent of that of the ions prior to their incorporation into the solid phase [52]. These results give rise to the question of whether this incorporation of water molecules into the surface could be the origin of the amorphisation of the outer surface of bone mineral nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, therefore, suggest that, in wet conditions, a large quantity of water molecules is not only strongly bound to but is also trapped within the amorphous surface layer. Since the arrangement of ions/molecules within the amorphous surface layer is sometimes seen as a reminiscence of the state in which the ions/molecules were prior to their incorporation into the solid phase [52], we can assume that these additional trapped water molecules form hydration spheres around the surface ions. Hence, the trapped water molecules might be part of the first hydration sphere of the surface ions, while the bound water molecules might be part of the second or third hydration sphere of the surface ions.…”
Section: mentioning
confidence: 99%